The tragic in disquiet and its destines - Gil, José; Vásquez Tamayo (Traductor), Carlos (Estudios de Filosofía, 2011)
Starting from the definition of what is tragic proposed by Hölderlin, the portuguese essayist José Gil strives to propose in this article how the Poetical Thought of Fernando Pessoa is separated from a tragic conception of existence, understood as a splitting, insoluble conflict, a fall into the abyss without reaching a bottom. He restores on the contrary an Immanent Materialism in Pessoa that would have as a condition the unceasing production of sensations, the invention of forms of existence through the means of written expression, the poet understood as voyager through sensations, an inventor of lines of escape, an experimenter of realities.